(untitled) (Comparative & International Education Series, 2021)
International scholars comprise an increasing number of faculty working in the US. Although they share many challenges with other professional migrants, the need to adapt to a new education system sets them apart. Here we consider some of the unique challenges facing international faculty, focusing particularly on challenges in the classroom. We finish by assessing the resources available from international scholar services to help with this transition. In a review of websites, we conclude that ample support is available to deal with practical issues such as getting visas, but little support is provided for adapting to a new teaching environment.